Critical Questions for Preclinical Trials on Safety and Efficacy of Vascular Endothelial Growth Factor-Based Therapeutic Angiogenesis for Ischemic Stroke - S. Manoonkitiwongsa, P. (CNS & Neurological Disorders - Drug Targets, 2011)
Therapeutic angiogenesis is a novel treatment for ischemic stroke, and vascular endothelial growth factor (VEGF) is a key angiogenic and neuroprotective pharmacological candidate for therapy. However, the greatest challenge of preclinical studies is demonstrating that VEGF-based therapeutic angiogenesis is safe and effective for ischemic stroke patients. This review presents the following crucial questions which must first be answered by preclinical studies before VEGF-based therapeutic angiogenesis advances to human stroke trials, (1) Does angiogenesis induced by VEGF monotherapy promote neuroprotection or further damage the nervous tissue? (2) Does angiogenesis by VEGF in combination with other agents (combination therapy) promote greater neuroprotection than monotherapy, and without additional side effects? (3) Which exogenous VEGF isoform best promotes angiogenesis and neuroprotection, with least adverse effects on other organs? (4) Does angiogenesis induced by exogenous VEGF produce similar results in different animal models of ischemic stroke, including variations in age, gender and coexisting chronic diseases? (5) Can angiogenesis be induced by exogenous VEGF without clinically-significant alterations of systemic hemodynamics? (6) Are gene therapy and stem cells more beneficial than recombinant protein for VEGF-based therapeutic angiogenesis? (7) What are the best routes, timing and duration for administering VEGF, and how do these parameters influence inflammation? (8) Does exogenous VEGF exacerbate inflammation when traumatic or other injuries are present with ischemia? (9) Are VEGF doses not causing tissue alterations at the light microscopy level associated with clinically-significant ultrastructural damages of the neurovascular unit? Both published and unpublished preclinical data from the author's laboratory are presented.
Keywords: vascular endothelial growth factor